Essays on competition, innovation and growth - Zanchettin, Piercarlo (2005)
The thesis collects four essays in the fields of competition and innovation economics. In chapter 1, we review the recent growth literature that analyses the effects of product market competition on growth. Contrary to the negative effect predicted by the early endogenous growth models, this literature emphasises that product market competition may foster innovation and growth. We argue that a common characteristic of this literature is a decrease in the intensity of technological competition relative to the early models, which seems to support the positive link between product market competition and growth.